2019
DOI: 10.35680/2372-0247.1371
|View full text |Cite
|
Sign up to set email alerts
|

Engaging under- and/or never-engaged populations in health services: A systematic review

Abstract: Patient engagement is a mechanism used to facilitate person-centred care, however, has not been realized in all patient populations. Often, many marginalized populations still remain under-and/or never-engaged. The purpose of this systematic review was to: 1) identify methods or interventions that have been used to engage under-and/or neverengaged populations in health services and 2) identify outcomes that are associated with engaging under-and/or neverengaged populations in health services. A comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Hence, the framework is consistent with literature that has identified that effective CCI is predicated on values and relationships, 32 positive attitudes, and behaviours 31 . The enhanced emphasis on trusting relationships, colearning, and valuing different perspectives as key mechanisms for success, is compatible with coproduction research, 33 and literature regarding CCI with diverse and under‐engaged populations 9,34 . It also reinforces that in addition to their lived experience of healthcare, consumers bring much knowledge, skill, and experience to CCI activities 35‐37 .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Hence, the framework is consistent with literature that has identified that effective CCI is predicated on values and relationships, 32 positive attitudes, and behaviours 31 . The enhanced emphasis on trusting relationships, colearning, and valuing different perspectives as key mechanisms for success, is compatible with coproduction research, 33 and literature regarding CCI with diverse and under‐engaged populations 9,34 . It also reinforces that in addition to their lived experience of healthcare, consumers bring much knowledge, skill, and experience to CCI activities 35‐37 .…”
Section: Discussionsupporting
confidence: 76%
“… 31 The enhanced emphasis on trusting relationships, colearning, and valuing different perspectives as key mechanisms for success, is compatible with coproduction research, 33 and literature regarding CCI with diverse and under‐engaged populations. 9 , 34 It also reinforces that in addition to their lived experience of healthcare, consumers bring much knowledge, skill, and experience to CCI activities. 35 , 36 , 37 The addition of the purpose and principles statements further increases the prominence of CCI core values.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition to education, interventions that address psychosocial factors are necessary. This may involve providing emotional support, counseling, and access to mental health services to help individuals overcome fear, denial, and other emotional barriers that impede timely action [38].…”
Section: Psychosocial and Behavioralmentioning
confidence: 99%